Serverless architecture with AWS - Gupta, Mohit; Krist, Stefan (Packt Publishing, 2019)
"Serverless Architectures with AWS begins by talking about the serverless model and getting started with AWS and Lambda. You'll also discover the main advantages and disadvantages of the serverless model through various use cases. You'll also explore other capabilities of the AWS Serverless Platform and see how AWS supports enterprise-grade serverless applications, with and without Lambda. From Compute to API Gateway, from storage to database, the fully managed services for building and running serverless applications on AWS are discussed in detail. Then, you'll use your learnings to deploy your first serverless project. You'll also explore the capabilities of serverless Amazon Athena, an interactive query service that makes it easy to analyze data directly in Amazon Simple Storage Service (Amazon S3) using standard SQL. Then, you'll learn about AWS Glue, a fully managed ETL service that makes it simple and cost-effective to categorize your data. You'll study how Amazon Kinesis makes it possible to unleash the potential of real-time data insights and analytics by offering capabilities, such as Kinesis Video Streams, Kinesis Data Streams, Kinesis Data Firehose and Kinesis Data Analytics. Last but not least, you'll learn to combine Amazon Kinesis capabilities with AWS Lambda to create lightweight serverless architectures."--Resource description page